Pengaruh Lama Fermentasi Terhadap Mutu Organoleptik pada Proses Pembuatan Teh Kombucha Bunga Telang (Clitoria ternatea L.) - Lia, Rosa; Shalehah, Almaratus; Jannah, Miftahul; Muslimin, Muhammad Imammul; Aini, Kurratul (Jurnal Kridatama Sains dan Teknologi, 2024)
Kombucha is a tea-based probiotic drink that has been dissolved with sugar and has been fermented using a mixture of yeast and bacteria, then forming a plate on its surface known as SCOBY (Symbiotic Culture of Bacteria and Yeast). This study was conducted to determine the effect of the fermentation of telang flower kombucha tea (Clitoria ternatea L.) on organoleptic quality which includes taste, aroma, and color. The method used in this study is an experimental method to test the effect of fermentation time on the organoleptic quality of telang flower kombucha tea which consists of 4 different treatments, namely fermentation time of 7 days, 10 days, 12 days and 14 days. The research results show that fermentation time has an influence on taste, aroma and color. A fermentation period of 14 days is recommended as the best treatment to produce butterfly pea flower kombucha tea, because it has the best organoleptic qualities which include a not strong sour and sweet taste, a distinctive sour kombucha aroma, and a clear dark purple col.